Drake makes a splash! - O'Ryan, Ray (O'Ryan, Ray. Galaxy Zack., 2014)
When summer arrives on Nebulon, Zack discovers that his best friend, Drake, is afraid to learn to swim and decides to teach him before they go on a trip to water-covered planet Araxie.